2019
DOI: 10.1002/slct.201901719
|View full text |Cite
|
Sign up to set email alerts
|

Substitution Effect on Luminescence of 5H‐Indeno[1,2‐b]pyridin‐5‐one Based Isomers

Abstract: A series of novel fluorescent isomers were designed by using 5H‐indeno[1,2‐b]pyridin‐5‐one (IP) as electron acceptor and triphenylamine (TPA) as electron donor, and were synthesized through Suzuki coupling reactions. The substitution position of TPA on IP was adjusted to form 6‐(4‐(diphenylamino)phenyl)‐5H‐indeno[1,2‐b]pyridin‐5‐one (IP‐6‐TPA), IP‐7‐TPA, IP‐8‐TPA, and IP‐9‐TPA. The photophysical, thermal, and electrochemical properties of these isomers were systematically studied through experimental and theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Interestingly, they observed that the positional isomers with the donor linked at the 7 or 8 position exhibited normal fluorescence behavior, whereas isomers (IP-6-TPA and IP-9-TPA) at the 6-or 9-position with a more twisted conformation displayed TADF characteristics (Scheme 49c). 249 Free radical-induced transformations of CÀH bonds have been adopted in the synthesis of an MR-TADF emitter. In 2020, Duan's group revealed the synthetic method involving free radicals for the construction of a bathochromic-shift B/Nbased MR-ATDF emitter, AZA-BN (Scheme 50).…”
Section: Free-radical-involved Càh Transformations For Accessing Tadf...mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, they observed that the positional isomers with the donor linked at the 7 or 8 position exhibited normal fluorescence behavior, whereas isomers (IP-6-TPA and IP-9-TPA) at the 6-or 9-position with a more twisted conformation displayed TADF characteristics (Scheme 49c). 249 Free radical-induced transformations of CÀH bonds have been adopted in the synthesis of an MR-TADF emitter. In 2020, Duan's group revealed the synthetic method involving free radicals for the construction of a bathochromic-shift B/Nbased MR-ATDF emitter, AZA-BN (Scheme 50).…”
Section: Free-radical-involved Càh Transformations For Accessing Tadf...mentioning
confidence: 99%
“…Interestingly, they observed that the positional isomers with the donor linked at the 7 or 8 position exhibited normal fluorescence behavior, whereas isomers (IP-6-TPA and IP-9-TPA) at the 6- or 9-position with a more twisted conformation displayed TADF characteristics (Scheme 49c). 249…”
Section: Preparing Tadf Emitters Through Non-transition Metal-promote...mentioning
confidence: 99%